Occlusion of the Anterior Cerebral Artery Mimicking a Cerebral Aneurysm: Clinical Presentation and Literature Review - Liu, Yang; Guo, Gaochao; Lin, Zhu; Zhao, Liming; Hernesniemi, Juha; Li, Chaoyue; Andrade-Barazarte, Hugo (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2021)
Background Intracranial aneurysms may be misdiagnosed with other vascular lesions such as vascular loops, infundibulum, or the stump of an occluded artery (very rare and reported compromising only the middle cerebral artery and the posterior circulation territory). Our aim was to describe a unique case of occlusion of an anterior cerebral artery mimicking a cerebral aneurysm in a probable moyamoya disease patient, and to highlight its clinical presentation, diagnosis, and management, and to perform an extensive literature review.Case A 67-year-old man suffering from recurrent dizziness for 3 months. Previous medical history was unremarkable. Brain magnetic resonance angiography (MRA) and digital subtraction angiography (DSA) demonstrated occlusion of the right middle cerebral artery (MCA) associated with a “probable moyamoya disease” and an aneurysm-like shadow protruding lesion at the anterior communicating artery (AcomA). Perfusion images showed ischemia along the right temporo-occipital lobe. Due to MCA occlusion with perfusion deficits and unspecific symptoms, we offered a right side encephalo-duro-myo-synangiosis (EDMS) and clipping of the AcomA aneurysm in one session. Intraoperatively, there was no evidence of the AcomA aneurysm; instead, this finding corresponded to the stump of the occluded right anterior cerebral artery (A1 segment). This segment appeared to be of yellowish color due to atherosclerosis and lacked blood flow. The patient underwent as previously planned a right side EDMS and the perioperative course was uneventful without the presence of additional ischemic attacks.Conclusion Arterial branch occlusions can sometimes present atypical angiographic characteristics that can mimic a saccular intracranial aneurysm. It is relevant to consider this radiographic differential diagnosis, especially when aneurysm treatment is planned.
Keywords: cerebral aneurysm; moyamoya disease; arterial occlusion; MRI; DSA